FCRL3 genetic variants drive autoimmune pathogenesis in multiple sclerosis and neuromyelitis optica spectrum disorders - Huang, Hui-Fen; Liu, Qi-Bing; Xu, Yong-Feng; Zhao, Gui-Xian; Liu, Hai-Peng; Yu, Hao; Wu, Zhi-Ying (Frontiers in Neurology, 2025)
ObjectiveThis study aims to investigate the association of Fc receptor-like 3 (FCRL3) gene variants with multiple sclerosis (MS) and neuromyelitis optica spectrum disorder (NMOSD) in a Chinese population cohort.MethodsIn Stage 1, 154 MS patients, 109 NMOSD patients, and 301 normal controls were recruited, Sequenom MassARRAY technology was used for genotyping single nucleotide polymorphisms (SNPs). Stage 2 involved an independent cohort of 95 MS patients, 139 NMOSD patients, and 226 normal controls. Two FCRL3 SNPs (rs7528684 and rs11264799) were determined using allele-specific polymerase chain reaction (PCR) with specific primers.ResultsAllele C of rs7528684 emerged as a protective factor for MS. Allele A of rs11264799 exhibited no significant effect on MS or NMOSD. A notable disparity in rs7528684 genotype distribution was observed between oligoclonal band (OCB)-positive and OCB-negative MS patients. Allele C of rs7528684 exhibited an association with OCB-positive MS patients.ConclusionThe findings suggest that the FCRL3 variant (rs7528684) is associated with MS rather than NMOSD. FCRL3 might significantly contribute to OCB synthesis, while the underlying mechanisms warrant further elucidation.